The effect of leverage, profitability, company size, proportion of institutional ownership, and corporate social responsibility on tax planning - Br Haloho, Yesicha Windi Yani; Rahmadhani, Sari (Jurnal Mantik, 2024)
The study aims to test and analyze the impact of leverage, Profitability, Corporate size, Proportion of institutional ownership, and Corporate social responsibility on Tax planning on companies in the basic industrial and chemical sectors listed on the Indonesian Stock Exchange in 2018-2022. The total population in this study is 73 companies in the basic and chemical industries sectors. The sampling technique in this study uses purposive sampling based on certain criteria, so samples obtained as much as 245 observation data from 49 companies. The data used in this study is secondary data. The data analysis technique used to analyze this study is a logistical regression test. The results show that leverage and corporate social responsibility hurt tax planning. Profitability has a positive impact on tax planning. As well as the company size and the proportion of institutional ownership do not influence tax planning